ANALISIS KEPUASAN PELANGGAN BENGKEL MOTOR YAMAHA SENTRAL PALEMBANG 2022-2023 - Novita, Novita; Widagdo, Herry (Publikasi Riset Mahasiswa Manajemen, 2023)
This study aims to determine the effect of trust, service quality, facilities, and price perceptions both partially and simultaneously. The sample in this study were 160 respondents using the Roscoe sampling method. Based on the results of the study, the variables of trust, service quality, facilities, and price perceptions simultaneously influence customer satisfaction.